KREDIBILITAS PEMBIMBING: FAKTOR YANG MEMPENGARUHI MOTIVASI MAHASISWA MENYELESAIKAN TUGAS AKHIR PERKULIAHAN - Laksana, Fauzi Putra; Winangsih, Rahmi; Framanik, Naniek Afrilla; Fajarwati, Noerma Kurnia (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
This study aims to examine the credibility of the resources held by the thesis supervisor and their influence on student motivation in completing the thesis. The independent variable in this study is lecturer credibility, while the dependent variable is student motivation. This study uses the Source Credibility theory which is broken down into three main dimensions, namely Expertise, Trustworthiness and Attractiveness. The research population is students of communication science study programs who are taking thesis in the odd semester of the 2018/2019 academic year totaling 170 students. Samples were taken as many as 63 respondents from the 10% precision Slovin formula with simple random sampling technique. Data were analyzed using SPSS version 23.00 including data quality tests, normality tests, correlation coefficient tests, linear regression tests and hypothesis tests. The results showed the credibility of the supervisor was in the good category with an average score of 68.85%. Student motivation in completing the thesis is also in the high category with an average score of 76.05%. The credibility of the supervisor has proven to have a significant positive effect on students' motivation to complete the thesis with an effect value of 21.2%.